Effects of Fermentation Conditions on the Production of Thermostable Lipase by Recombinant E. Coli - Ismail, Fadzlirahimi (2006)
A recombinant Escherichia coli BL21 (DE3) plysS (pGEX / T1S) strain harbouring thermostable lipase (E.C.3.1.1.3) gene from Geobacillus sp. was used through out this study. Lipase production was investigated using 2 L fermenter with 1.5 L working volume. Initial fermenter operation resulted in 11.07 U/mL activity with 24 h inoculum, temperature of 30°C, 250 rpm impeller speed and without pH and dissolve oxygen tension (DOT) control strategy. Optimisation of fermentation operation conditions such as inoculum age, temperature, impeller speed, airflow rate, pH and dissolve oxygen tension (DOT) control strategy throughout the fermentation were carried out and compared. A substantial high activity of lipase was detected during fermentation with 10 h inoculum. Lipase production was 41.18 U/mL activity which was comparable to previous optimised shake bottle and was 3.7 times higher than with 24 h inoculum. Increasing the cultivation temperature to 37°C, resulted in an increased of lipase production to 89.82 U/mL activity with highest cell mass attained of 6.63 g/L. However, no significant difference (41.18 and 46.71 U/mL activity) in lipase production was observed at temperature 30°C and 40°C, respectively. Lipase production increased with an increasing airflow rate, with highest production of 89.82 U/mL activity observed at 1.5 L/min (1 vvm). In contrast, lipase production decreased to 47.30 U/mL activity with higher airflow rate, which was 2 times lower than those obtained at low airflow rates. Further experiment on impeller speed showed only slight increased in lipase production. When impeller speed increased from 250 to 350 rpm, only slight increase of lipase production observed, from 89.82 U/mL to 93.03 U/mL activity. Higher and lower impeller speed showed no improvement in lipase production. Production time was reduced from 8 h to 5 h. Maximum cell mass decreased with increasing controlled pH and no improvement in overall productivity observed. At all dissolve oxygen control (DOT) strategy studied, no improvement in lipase production was observed. Highest production was observed in fermentation when DOT was controlled at 80% saturation which gave productivity of 4.85 U/mL.h.